Fenomena turnover intention pada Generasi Z dalam revolusi industri 5.0 - Wibowo, Frendy; Sosilowati, Eny; Setiyawan, Adi Andika (Nur Science Institute, 2024)
Gen Z as a workforce filler provides great opportunities for company development, but problems arise when various surveys show that Generation Z tends to change jobs (turnover intention). This study aims to analyze the phenomenon of turnover intention in Generation Z. This type of research is quantitative and uses primary data obtained directly from questionnaires distributed to respondents. The population of this study was Gen Z in Surakarta, who worked in various fields and had one year of work experience, while the research sample was 100 Gen Z in Surakarta. The sampling technique was purposive sampling. Hypothesis testing in the study used multiple linear regression. The results showed that transformational leadership, work-life balance, and job stress significantly affected turnover intention in Gen Z. Gen Z, as productive youth, needs guidance from transformational leadership to achieve work-life balance and prevent stress in work. Turnover intention must be an important concern for companies by creating work balance and minimizing factors that trigger work stress.